(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Shalakya tantra is one of the specialties described in Ashtanga Ayurveda which deals with diseases with sense organs occurring in Urdhwanga (above the clavicle). The eyes are one of the utmost sensitive and susceptible organs in the body. Acharya Sushruta has mentioned 76 Netra roga while Acharya Vagbatta and Sharangadhara have mentioned 94. Susruta Samhita and Ashtanga Hridaya Samhita respectively mentions eleven and thirteen Shuklagata roga (diseases of the sclera) Prastari arma, Shukla arma, Rakta arma, Adhimamsa arma and Snayu arma are 5 types of Arma which are classified under the Suklagata roga. Among the five types, Prastari arma is characterized by gradually developing wing like encroachment of Shuklamandala from either Kaninika sandhi (inner canthus) or Apanga sandhi (outer canthus) towards Krishnamandala, which causes discomfort in the eye. Prastari arma can be correlated with Pterygium and it is more common among people who are residing in tropical and subtropical areas. Risk factors are exposure to sunlight, dry and dusty climate and smoke. Pterygium is a common ocular disorder in India due to disease favorable geographic and climatic conditions. In this clinical study, an effort has been made to establish an effective Ayurveda treatment protocol in the management of Prastari arma. A 35 years old female patient from Jamnagar came to OPD of Shalakya tantra with chief complaints of pinkish, triangular shaped elevation in her right eye with foreign body sensation, dryness, burning sensation and sensitivity to bright light. The patient was diagnosed as having Prastari arma and was given Elaneer kuzhambu anjana, Triphala kwatha parisheka with Triphala churna orally for thirty days. The effectiveness of the line of treatment was assessed on the basis of signs and symptoms before and after the treatment. A special scoring system was adopted for assessing signs and symptoms of the disease. The medication was found safe and effective in curing the disease condition of Prastari arma. Keywords: Pterygium, Suklagata roga, Urdhwanga, Prastari arma 1Department of Shalakya Tantra, Institute for Post Graduate Teaching and Research in Ayurveda, Gujarat Ayurved University, Jamnagar, India. 2Faculty of Health Sciences, Symbiosis International University (Deemed University), Maharashtra, Pune, India. 3Department of Rasa Shastra & Bhaishajya Kalpana, Institute for Post Graduate Teaching and Research in Ayurveda, Gujarat Ayurved University, Jamnagar, India. *Correspondence: Sooriyaarachchi B.S.M.M., P.G. Scholar, Department of Shalakya Tantra, Institute for Post Graduate Teaching and Research in Ayurveda, Gujarat Ayurved University, Jamnagar, India.